STUDI KAPASITAS DEBIT AIR TANAH PADA AKUIFER TERTEKAN DI KOTA MALANG - Abduh, Moh. (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
Target of this study is to know estimate of potency of groundwater discharge, available optimum discharge and groundwater discharge which have been taken or exploited in Malang town. Analysis method of this study are Pumping Test method (Long Period Test), with the well test and aquifer test. The result of the analysis of performance aquifer test from the 18 well to be taken 3 well the type of flow is unsteady state flow and 15 well is steady state flow. According to the well test and aquifer test, groundwater potency (Qp) in Malang town between 1,22 up to 15,64 ltr/sec or 105,41 up to 1.351,30 m3/day. The optimum discharge (Qopt.) available between 0,66 up to 9,03 ltr/sec or 57,00 u to 780,00 m3/day, while operation discharge of the well according to the existing data (Qop) between 1,50 up to 10,00 ltr/sec or 129,60 up to 864,00 m3/day exceeding of optimum discharge. Influence effect of abundant exploited of groundwater is degradation of surface of groundwater and causing ugly to condition of the availibility of water. Stages, steps management of groundwater and conservation for example by taking care of continuity of environment and control groundwater exploration and also pay attention influence of pumping and degradation of surface of groundwater, by determining apart minimum (2R) between well and pumping discharge do not exceed available optimum discharge. With management stages, steps like expected above mentioned of change or degradation of surface of groundwater effect of pumping do not exceed boundary.Keywords: Groundwater potency, Optimum discharge, Operation discharge, Pumping Test, Steady and Unsteady flow.